A Legal Comparison Regarding Abuse of Dominant Position by Online Platforms - Nasir, Rifqi Ridlwan (Jurnal Persaingan Usaha, 2025)
The digital market is defined by features such as platform-based operations, extensive use of data, interactions across multiple market sides, and the influence of network effects. Through the use of data, businesses can forecast market movements and analyze consumer behavior, potentially leading to unfair competitive practices. This study is classified as normative legal research. It employs a statutory-regulatory approach, a conceptual framework, and a comparative analysis. The research method involves a literature review supported by qualitative analytical techniques. Considering regulations in various countries, the utilization of consumer data by online platforms is a key factor in evaluating their market dominance and preventing abuse of dominant position. It is essential for the government to establish a the provisions for the use of consumer or user data on online platforms as one of the characteristics of their dominant position through Government Regulation that harmonizes the provisions of Act Number 5 of 1999, Act Number 8 of 1999, and Act Number 27 of 2022, and regulatory framework to classify dominant online platforms like "gatekeepers" designation by considering factors such as a company's financial strength and data processing capabilities.